Barriers and opportunities for cleanliness of shared sanitation facilities in low-income settlements in Kenya - Sheillah N. Simiyu; Raphael M. Kweyu; Prince Antwi-Agyei; Kwaku A. Adjei (BMC, 2020)
Abstract Background The sharing of sanitation facilities is a common practice in low-income areas in sub-Saharan Africa. However, shared sanitation is currently categorized as a limited sanitation service, and may therefore not count towards meeting the global goals. These shared facilities are often the only option available for most residents in low-income settlements, and improving their cleanliness and overall management is key to reducing open defecation and risk of disease. This study sought to investigate barriers and opportunities for improved cleanliness of shared sanitation facilities in low-income settlements of Kisumu city, Kenya. Methods Thirty-nine in-depth interviews and 11 focus group discussions were held with residents - mainly tenants and landlords - of a low-income settlement in Kisumu. Analysis followed a thematic approach to define the problem, specify the target behaviour and identify the changes needed. Results Sanitation facilities were mainly pit latrines, typically shared among landlords and tenants. Participants singled out behavioural (poor use of the shared toilets) and social (lack of cooperation in cleaning) challenges that led to unclean shared toilets. Available opportunities for improvement included instituting clear cleaning plans, improving communication among users, and enhanced problem-solving mechanisms between landlords and tenants. These approaches could form the basis for designing intervention strategies for improving the cleanliness of shared sanitation facilities. Conclusion The results highlight the need to focus on social aspects for improvement of cleanliness in shared sanitation facilities in low-income settlements. Through a social approach, shared sanitation facilities can be managed appropriately to provide the millions of low-income residents in Kenya an opportunity to access sanitation. This study provides further evidence on approaches for improved management of shared sanitation facilities in line with the World Health Organization's (WHO) Joint Monitoring Program's (JMP) recommendation for high quality shared facilities.